IBM tape library guide for open systems - Coyne, Larry; Browne, Simon; Engelbrecht, Michael (IBM redbooks., 2016)
This IBM® Redbooks® publication presents a general introduction to the latest IBM tape and tape library technologies. Featured tape technologies include the IBM LTO Ultrium and Enterprise 3592 tape drives, and their implementation in IBM tape libraries. This 13th edition includes information about the latest enhancements to the IBM TS4500 enterprise tape library. In particular, it includes details about the latest TS4500 High Availability feature and its elastic capacity option. This book also provides details about the new TS7650G IBM ProtecTIER® gateway model DD6, contains technical information about each IBM tape product for open systems, and includes generalized sections about Small Computer System Interface (SCSI) and Fibre Channel connections and multipath architecture configurations. This book also covers tools and techniques for library management. It is intended for anyone who wants to understand more about IBM tape products and their implementation. It is suitable for IBM clients, IBM Business Partners, IBM specialist sales representatives, and technical specialists. If you do not have a background in computer tape storage products, you might need to read other sources of information. In the interest of being concise, topics that are generally understood are not covered in detail.